Plasma 1-palmitoyl-2-linoleoyl phosphatidylcholine. Evidence for extensive phospholipase A1 hydrolysis and hepatic metabolism of the products - Scagnelli, G.P.; Cooper, P.S.; VandenBroek, J.M.; Berman, W.F.; Schwartz, C.C. (The Journal of biological chemistry, 1991)
1-Palmitoyl-2-linoleoyl phosphatidylcholine (PLPC) labeled in either the choline, glycerol, palmitate, or linoleate component in reconstituted rat high density lipoprotein (rHDL), was administered by vein to rats with bile fistula and taurocholate infusion. PLPC disappeared from plasma in a monoexponential fashion with a half-life of 50 min. A small fraction, about 14%, of PLPC disappearance was due to removal of linoleate from the sn-2 ester bond to form plasma cholesterol esters, presumably by lecithin-cholesterol acyltransferase. Otherwise, nearly all of the PLPC components that disappeared from blood in 1 h were recovered in the liver. The choline, glycerol, and linoleate components appeared predominantly in hepatic phosphatidylcholine (PC). These three components remained together in the liver with similar fractions of each in individual PC molecular species, most notably 1-stearoyl-2-linoleoyl-PC and dilinoleoyl-PC as well as PLPC. However, the palmitate component was spread among hepatic triglyceride, free fatty acid, other phospholipids, and all palmitate-containing molecular species of PC. Less than 2% of any administered PLPC component appeared in 1-stearoyl-2-arachidonyl-PC, the major species by mass in the liver. The palmitate component from plasma PLPC appeared in biliary PC at a more rapid rate than glycerol and linoleate components; the latter components appeared in bile in identical fashion. The results show that about two-thirds of plasma PLPC disappearance is due to phospholipase A1 hydrolysis, probably hepatic lipase. The putative produce, 2-linoleoyl-lysoPC, is efficiently reacylated with a saturated fatty acid in the liver, conserving PC.